Metafiction in “El día que murió papá,” by Silvia Aguilar Zéleny - Arias Sánchez, Erika Aguedha (2022)
This article analyzes the short story “El día que murió papa” [The day that father died], by Sylvia Aguilar-Zéleny in Nenitas (2013). It is suggested that the use of metafiction shows the characters’ inner borders. By breaking with the traditional notions of border literature and approaching it from a perspective beyond that of a geographical space or a linguistic phenomenon, the author problematizes the construction of the protagonists’ identity. Through metafiction and its linguistic concretion, she reflects on how different symbolic boundaries are manifested in this literature.